Hysteretic behaviour of high strength S690 steel materials under low cycle high strain tests. (15th June 2018) - Ho, H.C.; Liu, X.; Chung, K.F.; Elghazouli, A.Y.; Xiao, M.
Highlights: S690 steel is shown in tests to be strong and ductile. Test coupons can deform up to a strain of ±10% under cyclic actions. Different hysteretic loops are obtained at different target strains. Use instantaneous diameters of test coupons to determine true stresses. Stress strain curves from monotonic and cyclic tests are different. Abstract: This paper describes a detailed experimental investigation into structural behaviour of S690 steel materials under both monotonic and cyclic loading conditions. In addition to 6 monotonic tensile tests, which were conducted to establish basic mechanical properties, 36 cyclic tests were then carried out in order to examine hysteretic behaviour of the S690 steel materials under various target strains and loading frequencies. The experimental arrangements used for the monotonic and the cyclic tests are described, and a detailed account of the test results is provided. The monotonic tests showed that all the S690 steel specimens satisfied the ductility requirements stipulated in current European provisions which are typically based solely on monotonic behaviour. In the cyclic tests, most specimens were able to complete 20 cycles with target strain amplitudes of ±2.5%, ±5.0%, ±7.5%, and ±10.0%, under loading frequencies of 0.1, 0.5, 1.0 and 2.0 Hz. However, some specimens fractured at the 20th cycle when the target strains were ±10.0% irrespective of the loading frequency. Additionally, significant strength enhancement due to strain hardening was observed and quantified in the cyclic tests, depending on the level of target strains. The results additionally illustrated the importance of using actual instantaneous cross-sectional diameters for evaluating true stresses in order to obtain actual representative hysteretic curves. In general, the study highlights the importance of establishing seismic ductility requirements based on cyclic tests, particularly for high strength steel materials. It also provides a detailed assessment of the hysteretic characteristics, which can be directly employed to develop reliable constitutive models for high strength S690 steel materials under seismic loading conditions.